Pengaruh Penambahan Tepung Daun Kelor (Moringa oleifera) dengan Level Berbeda terhadap Kualitas Fisik Bakso Daging Ayam Broiler - Yulisriani, Rina; Qurniawan, Anas; lestari, Ayu; Irmawaty, Irmawaty; Nurul Afiyah, Dyah (Universitas Islam Kadiri, 2024)
This study aims to determine the effect of the addition of moringa leaf flour (Moringa oleifera) with different levels on the physical quality of broiler meatballs. The study was experimental, using a Complete Random Design, with 4 treatments and 3 replicates. Each test uses 3 meatballs with the given treatment (P0): 0% moringa leaf flour (Moringa oleifera), P1 (2.5%) moringa leaf flour (Moringa oleifera), P2 (30%) moringa leaf flour (Moringa oleifera), P3 (35%) moringa leaf flour (Moringa oleifera). The parameters tested are pH, Cooking Shrinkage, Lentility. Organoleptok test (hedonic test) and hedonic quality or the level of the panelists' preference for the product. The results obtained were that the physical quality test did not have a significant effect (P>0.05) on pH, sour shrinkage and elasticity. The results of the hedonic test had a significant effect (P<0.05) on taste, aroma, color and texture. The results obtained on hedonic quality are to have a significant influence (P>0.05) on pH, sour shrinkage and elasticity. The results of the hedonic test had a significant effect (P<0.05) on taste, aroma, color and texture. The results obtained on hedonic quality are to have a real influence (P<0.05) on taste, aroma, color, texture and chewiness.